Comparison of harmonic scalpel versus Milligan Morgan technique in haemorrhoidectomy patients - Ahmad, Muhammad; Abbas, Syed Tatheer; Javaid, Amna; Arshad, Naveed; Shair, Falak (Journal of the Pakistan Medical Association, 2021)
Objectives: To assess the comparison of harmonic scalpel versus Milligan Morgan technique in patients undergoing haemorrhoidectomy. Methodology: This randomized controlled trial study was conducted at General Hospital, Lahore, from March 2019 to September 2019. Informed consent was obtained from eligible 60 patients. Patients were randomly divided into two equal groups. In group-A, haemorrhoidectomy was conducted according to the harmonic scalpel method. In group-B, open haemorrhoidectomy was performed by the Milligan Morgan procedure. Data was assembled through a designed questionnaire and investigated via SPSS version 25. Data were stratified for descriptive statistics, level of haemorrhoids and period of haemorrhoids. Post-stratification, independent sample t-test was used. Results: Mean age of both groups patients were 44.6±7.6 and 43.8±8.2 years, respectively. In group-A, mean operative time was 20.8±2.8 minutes, while 26.5±2.8 minutes in group-B, which was statistically significant with p-value of 0.001. In group-A, mean convalescence period was 9.7±2.9 days, while 13.4±3.7 days in group-B, which was statistically significant with p-value of 0.001. The mean convalescence period with harmonic scalpel method was 7.4 days (range 5–14, SD 3.6) versus 18.6 days (range 7–30, SD 5.4) with Milligan Morgan technique (P?0.001). This research observed that harmonic scalpel method required almost six weeks for complete wound healing, whereas in Milligan Morgan technique, complete wound healing was achieved after three months (P<0.05). Conclusion: Harmonic scalpel haemorrhoidectomy found an advantageous method when assessing the operative time and convalescence period. Hence, Harmonic scalpel haemorrhoidectomy can be adapted as a safe and effective alternative method for treating symptomatic haemorrhoids. Continuous...